Impact of Nonlinear Thermal Radiation on MHD Nanofluid Thin Film Flow over a Horizontally Rotating Disk - Zahir Shah; Abdullah Dawar; Poom Kumam; Waris Khan; Saeed Islam (Applied Sciences, 2019)
Nanoscience can be stated as a superlative way of changing the properties of a working fluid. Heat transmission features during the flow of nanofluids are an imperative rule from the industrial and technological point of view. This article presents a thin film flow of viscous nanofluids over a horizontal rotating disk. The impact of non-linear thermal radiation and a uniform magnetic field is emphasized in this work. The governing equations were transformed and solved by the homotopy analysis method and the ND-Solve technique. Both analytical and numerical results are compared graphically and numerically, and excellent agreement was obtained. Skin friction and the Nusselt number were calculated numerically. It is concluded that the thin film thickness of nanofluids reduces with enhanced values of the magnetic parameter. In addition, the nanofluid temperature was augmented with increasing values of the thermal radiation parameter. The impact of emerging parameters on velocities and temperature profiles were obtainable through graphs and were deliberated on in detail.